The design-resource-opportunity connection of entrepreneurship : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Management, Massey University, Albany, New Zealand - Baeyertz, Karen Eula (Massey University, 2010)
This study explored the relatively uncharted territory of entrepreneurship as a design process. It distilled the central components underlying this design process in terms of resource and opportunity connections. Adoption of an entrepreneurial capital framework was invaluable for gaining insight into the complex process of resource use and acquisition. An interpretive phenomenological approach was used to research the entrepreneur's actual lived experience of opportunity development and new venture creation. Findings were gleaned from fourteen entrepreneurs in the knowledge intensive technology sector in New Zealand. In-depth interviews enabled the participants to tell their stories of how they enacted opportunity. Two metaphors were explored with each of the interviewees. The first metaphor was introduced in order to comprehend how opportunity was perceived: Was it perceived as a mountain waiting to be climbed – opportunity discovery? Or was it perceived as a mountain that needed to be built - a creation view of opportunity? In order to understand resource interactions and relationships, the second metaphor explored a concept dear to the New Zealand psyche; that of No. 8 wire ingenuity in adapting to circumstance. Resource use and development was also investigated within the construct of bricolage. A key finding was that the design process of entrepreneurship involved the exercise of resources - those at hand in the inner resource domain of initial entrepreneurial capital and also augmented entrepreneurial capital accessed in the external resource domain. The centrality of human capital in the form of prior knowledge and industry experience that is embedded in the entrepreneur was highlighted. Learning by doing and knowledge development with customers, via a process of co-construction was significant. Entrepreneurs employed a number of strategies to overcome the liabilities of size and newness and importantly the generation of symbolic capital enabled establishment of legitimacy in the eyes of their stakeholders. Social and financial bricolage was practised by some entrepreneurs to 'make do' with their existing resources.
Keywords: Entrepreneurship; Management; Design; New Zealand; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management